BEYOND GRIEF AND ANGER: ANTARAXIA IN RĀMĀYAṆA SPIRITUALITY - I Komang Suastika Arimbawa (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The concept of antaraxia has deep relevance in Hindu spirituality, especially in the teachings of the Rāmāyaṇa. This epic describes how the principle of inner peace can be achieved through the path of bhakti, which is total surrender to God. This study analyzes how the spiritual values in the Rāmāyaṇa, especially through the characters of Rāma, Sītā, Bharata, and Hanuman. These characters represent the seek for inner peace amidst life's suffering and challenges. In the context of Hindu philosophy, the teachings of bhakti not only function as a means of achieving moksa, but also as a solution to the existential problems of modern humans filled with anxiety and conflict. This study uses a qualitative approach with text analysis of the primary sources of the Rāmāyaṇa and various interpretations from classical and modern Hindu literature. The results of this study indicate that the teachings of bhakti in the Rāmāyaṇa can provide deep insights into how to achieve inner balance and face the challenges of contemporary life. Thus, the legacy of Hindu philosophy remains relevant to respond human spiritual problems in the modern era.